Estimation Spatial Distribution of Sodium Adsorption Ratio (SAR) and Residual Sodium Carbonate (RSC) in Groundwater of Tando Muhammad Khan Pakistan - Benish Nawaz Merani,; Saghir Ahmed Sheikh,; Mahvish Jabeen Channa,; Aasia Akbar Panhwar ,; Aijaz Hussain Soomro, (Journal of Pharmacy and Nutrition Sciences, 2014)
This study was conducted to evaluate factors regulating groundwater quality in an area with agriculture as main use. Water samples for determining the water quality were collected in one liter polyethylene bags by observing standard sample collection method. It was ensured that sample collection sites must be at least 500 feet away from each other. Sodium Adsorption Ratio (SAR) and Residual Sodium Carbonate (RSC) were determined from the collected water and it was observed that in Tando Muhammad Khan taluka, the Sodium Adsorption Ratio (SAR) in the samples ranged from 11.06 to 53.29, the highest (53.29) SAR was in UC Tando Saindad, while lowest (11.06) in the sample collected from UC-2 of Tando Muhammad Khan. The Residual Sodium Carbonate (RSC) in 36 collected groundwater samples ranged from 0.61 to 5.15 meq/l, the highest (5.15 meq/l) was in UC Tando Saindad, while lowest (0.61) in the sample collected from UC-3 of Tando Muhammad Khan. It was concluded that the SAR levels of groundwater samples indicated an alarming situation and most of the ground-water samples had SAR (<7.5 meq/l) and RSC (<2.0 meq/l) above permissible limits of WHO for agriculture use therefore, it is not suitable for agriculture as well as drinking.